2011
DOI: 10.1590/s0006-87052011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield of dual-purpose wheat cultivars as affected by nitrogen and cuttings

Abstract: The aim of this work was to evaluate the effect of nitrogen fertilization and aerial part cuts on yield components, grain yield and quality of the grains for dual-purpose wheat cultivars. The experiment was carried out between May and November 2007 and the experimental design was randomized complete blocks with three replications. The main causes of variation were dual-purpose wheat cultivars (BRS Figueira, BRS Umbu, BRS Guatambu and BRS Tarumã), nitrogen doses (0, 45, 90, 135 and 180 kg ha -1 ) and cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Several studies have been conducted to evaluate the correct time of nitrogen fertilization on wheat crop under Brazilian tropical conditions (Silva et al, 2008;Megda et al, 2009;Espindula et al, 2010;Hastenpflug et al, 2011;Teixeira Filho et al, 2011Espindula et al, 2013. These studies take into account the application of nitrogen fertilizer at sowing and topdressing and suggest that N application just at sowing is enough to provide N during crop cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the correct time of nitrogen fertilization on wheat crop under Brazilian tropical conditions (Silva et al, 2008;Megda et al, 2009;Espindula et al, 2010;Hastenpflug et al, 2011;Teixeira Filho et al, 2011Espindula et al, 2013. These studies take into account the application of nitrogen fertilizer at sowing and topdressing and suggest that N application just at sowing is enough to provide N during crop cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In Paraná, there are three different regions that produce wheat, and BRS Tarumã wheat is recommended only for region 1 (South-Central region and southeast Paraná, represented by Ponta Grossa, Guarapuava, and Palmas), while western Paraná, in the Marechal Cândido Rondon region, belongs to region 3, suitable for producing wheat adapted warm weather, moderately dry climate, and low altitude (MONTECELLI et al, 2014). Hastenpflug et al (2011) reported BRS Tarumã wheat productivities of 1362.15 kg ha -1 , 1175.25 kg ha -1 , and 891.44 kg ha -1 without cuts, with one cut, and with two cuts, respectively, in Pato Branco (PR, Brazil). These results were superior to the productivity in this experiment.…”
Section: Without Grazing One Grazing Vs Without Grazing Two Grazings mentioning
confidence: 99%
“…It is also important that there is no excessive trampling so that the soil porosity is not compromised, as this consequently impairs water infiltration and soil aeration, which contribute to the development of the summer crops' deep roots. In addition, the end of the grazing period must be before the elongation of the internodes of the plants, and must be timed so that the residual height of the crops assures a minimum of 2 t ha -1 of haystack on the stubble (BARTMEYER et al, 2011;CRUZ et al, 2010;HASTENPFLUG et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations